El relato egipcio de Unamón. Las relaciones entre Egipto y la costa sirio-palestinense durante la Edad del Hierro, desde la literatura, la arqueología y la historia - Belén Castro, María (El Colegio de México, 2012)
The aim of this article is to analyse the relationships between Egypt and the Syro-Palestinian Coast during Iron Age I. The Egyptian tale of Wenamun—which describes the journey of this official to the Lebanon coast—, has been studied by many scholars as a primary source to describe the period. However, we will discuss here this use: we will explain some considerations about the sources nature and the work that scholars should do with them. Furthermore, we will present some archaeological evidence that show the relationship between the regions. In this way, we will try to create a tension between the expressed by the literary text and the evidence from material rests. We consider the former as a valid resource for the analysis, because it may show us different expressions about the issues of a specific society.